A low chloride ion leaching gypsum mortar and preparation method thereof

By using components such as tricalcium aluminate, tetracalcium aluminate, fly ash and hydrotalcite in gypsum mortar, the leachate rate of chloride ions is reduced, the performance degradation and corrosion problems caused by chloride ions in gypsum products are solved, and high-quality gypsum product production is achieved.

CN116177977BActive Publication Date: 2025-04-18LIAONING RUIFENG NEW BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211721127.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-18
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Existing gypsum products contain a large amount of chloride ions, leading to the formation of chloride salt, reducing the bonding and mechanical properties of gypsum products, and corrosively affecting materials such as steel bars, affecting use.

Method used

Low-chlorine ion leaching gypsum mortar is used, and its raw materials include desulfurization gypsum, tricalcium aluminate, tetracalcium aluminate, fly ash, hydrotalcium powder and retarder. Through the chemical combination of tricalcium aluminate, tetracalcium aluminate and chloride ions, the physical adsorption of hydrotalcium, and fly ash increase density and reduce the chloride ion leachate.

Benefits of technology

It effectively reduces the chloride ion leachate rate in gypsum mortar and improves the quality of gypsum products. This method is green and environmentally friendly, does not increase construction cost and difficulty, and has no significant adverse impact on the performance of gypsum mortar.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a low chloride ion leaching gypsum mortar and a preparation method thereof. The gypsum mortar comprises the following components by weight: 65-80 parts of desulfurized gypsum, 3-6 parts of tricalcium aluminate, 3-5 parts of tetracalcium aluminoferrate, 10-15 parts of fly ash, 5-10 parts of hydrotalcite, 0.2-0.5 parts of rubber powder and 0.01-0.03 parts of retarder. The preparation method comprises the following steps: adding rubber powder and retarder into water, stirring evenly with a stirrer to obtain an admixture solution; mixing desulfurized gypsum, tricalcium aluminate, tetracalcium aluminoferrate, fly ash and hydrotalcite powder evenly to obtain a mixed powder; mixing the admixture solution and the mixed powder evenly to obtain a low chloride ion leaching gypsum mortar. The present invention adopts the chemical combination of tricalcium aluminate, tetracalcium aluminoferrate and chloride ions, and utilizes the physical adsorption of hydrotalcite porous medium to reduce the chloride ion leaching rate, and simultaneously utilizes the addition of fly ash to increase the compactness of gypsum mortar, reduce chloride ion transmission, and further reduce the chloride ion leaching rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and particularly relates to a low-chloride ion gypsum mortar and a preparation method thereof. Background Art

[0002] Construction sand powder requires a large amount of gypsum. At the same time, the reserves of natural gypsum mines for producing gypsum are seriously insufficient. Every year, 70% of the country's gypsum raw materials need to be supplemented from industrial by-product gypsum, which has seriously restricted the sustainable and high-quality development of the domestic gypsum industry and related industries.

[0003] The main problem with using industrial by-product gypsum is that it contains a large amount of impurities that affect its practical application. For example, desulfurized gypsum contains a large amount of chloride ions. The introduction of chloride ions is mainly caused by the introduction of limestone minerals in the desulfurization process and the long-term circulation of cooling water in the desulfurization process. The presence of chloride ions in desulfurized gypsum will form chloride salts in the gypsum product. Since most chloride salts have high solubility, they easily absorb moisture at the interface of gypsum products to form salt films, thereby forming a stratification effect between crystals, reducing the bonding and mechanical properties of gypsum products. In addition, the presence of chloride ions will also corrode nails, steel bars, etc. that come into contact with gypsum products during service, thus affecting the use of desulfurized gypsum.

[0004] Therefore, developing a low chloride ion leaching gypsum mortar is of great significance for improving the utilization rate of industrial by-product gypsum and improving the quality of gypsum products. Summary of the invention

[0005] The technical task of the present invention is to provide a low chloride ion leaching gypsum mortar and a preparation method thereof in view of the deficiencies of the above prior art, which can effectively reduce the chloride ion leaching rate of the gypsum mortar and improve the quality of gypsum products.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a low chloride ion leaching gypsum mortar, wherein the raw materials include the following components by weight: 65-80 parts of desulfurized gypsum, 3-6 parts of tricalcium aluminate, 3-5 parts of tetracalcium aluminoferrite, 10-15 parts of fly ash, 5-10 parts of hydrotalcite, 0.2-0.5 parts of rubber powder and 0.01-0.03 parts of retarder.

[0007] Furthermore, the desulfurized gypsum is a dry powder with a particle size of 20 to 50 μm, and the specific operation is: the desulfurized gypsum is steamed in an autoclave with saturated steam, dried at 50 to 60°C and then sieved, and the particle size of the desulfurized gypsum after sieving is 20 to 50 μm.

[0008] Furthermore, the tricalcium aluminate is prepared by grinding analytically pure calcium carbonate and aluminum oxide in a molar ratio of 3:1, mixing them uniformly, and calcining them at high temperature.

[0009] Furthermore, the particle size of the tetracalcium aluminoferrite is 20 to 30 μm.

[0010] Furthermore, the fly ash is low-calcium fly ash, wherein the CaO content is ≤10wt%.

[0011] Furthermore, the hydrotalcite is one or more of magnesium-aluminum hydrotalcite or hydrotalcite-like compounds.

[0012] Furthermore, the rubber powder is any one of industrial redispersible latex powder and building instant rubber powder.

[0013] Furthermore, the retarder is sodium alginate, and the purity is ≥90wt%.

[0014] The present invention also provides a method for preparing the low chloride ion leaching gypsum mortar, comprising the following steps:

[0015] S1: Add rubber powder and retarder into water and stir evenly with a mixer to obtain an admixture solution;

[0016] S2: Evenly mix desulfurized gypsum, tricalcium aluminate, tetracalcium aluminate ferroferrate, fly ash and hydrotalcite powder to obtain a mixed powder;

[0017] S3: The admixture solution prepared in S1 and the mixed powder prepared in S2 are mixed evenly to prepare low chloride ion leaching gypsum mortar.

[0018] Furthermore, in the preparation of the low chloride ion leaching gypsum mortar, the amount of water added in S1 is 30% to 45% of the total mass of the powder in S2.

[0019] In order to facilitate the understanding of the control mechanism of the present invention, it is necessary to explain the gypsum chloride ion leaching process as follows: At present, the two main methods for chloride ion removal are chemical adsorption and physical adsorption. Studies have shown that the content of tricalcium aluminate, tetracalcium aluminoferrate, etc. in cement is positively correlated with the ability to bind chloride ions. The chemical binding mechanism is that tricalcium aluminate reacts with chloride ions to form F salt (C3A·CaCl2·10H2O) and its solid solution (Ca2Al(OH)6Cl·2H2O), thereby reducing the chloride ion content. In addition, the hydration product monosulfide calcium sulfoaluminate (AFm) phase is converted into F salt through a chemical adsorption mechanism or anion exchange mechanism. In the chemical adsorption mechanism, due to the positively charged [Ca4Al2(OH)12] 2+ Adsorbs negatively charged Cl- in the pore fluid to form electrically neutral F salts; in the anion exchange mechanism, it is the anion SO4 in the AFm phase interlayer 2- 、CO3 2-, OH- and Cl- are exchanged to form F salts, thereby reducing the chloride ion content. However, chemical adsorption will form other hydration products in gypsum, and is generally used in cement-based materials. For products with high gypsum purity requirements, there are certain limitations. In addition, physical adsorption can be used to treat the chloride ions in desulfurized gypsum, and porous materials are generally used for treatment. In addition, the chloride ion leaching rate in gypsum mortar can also be reduced by increasing the density of gypsum mortar. The present invention mainly changes the hydration process of tricalcium aluminate by adding hydrotalcite and fly ash, thereby controlling the amount of tricalcium aluminate and the hydration product AFm, thereby affecting the amount of free chloride ions and greatly improving the chloride ion leaching effect. Different from the traditional chemical adsorption or physical adsorption mechanism, this method mainly achieves chloride ion control by controlling the hydration process of aluminate cement.

[0020] Therefore, the beneficial effects of the present invention mainly include:

[0021] (1) The chemical combination of tricalcium aluminate, tetracalcium aluminoferrate and chloride ions is used to reduce chloride ion leaching.

[0022] (2) Utilize the physical adsorption effect of hydrotalcite porous media to reduce chloride ion leaching.

[0023] (3) The addition of fly ash can increase the density of gypsum mortar, reduce chloride ion transmission, and thus reduce the chloride ion leaching rate.

[0024] The above technical solution can reduce the chloride ion leaching rate without adversely affecting the performance of gypsum mortar, is green and environmentally friendly, and does not increase construction costs and construction difficulty.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The chloride ion leaching rate is significantly reduced and is easy to adjust and control;

[0027] (2) Green and environmentally friendly, non-toxic;

[0028] (3) No significant adverse effect on the performance of gypsum mortar. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0031] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0032] Implementation 1

[0033] The low chloride ion leaching gypsum mortar described in this embodiment comprises the following components in parts by weight: 70 parts of desulfurized gypsum, 3 parts of tricalcium aluminate, 3 parts of tetracalcium aluminoferrate, 13.79 parts of fly ash, 10 parts of hydrotalcite, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0034] The desulfurized gypsum is steamed in an autoclave with saturated steam, dried at 50-60°C and then sieved, and the particle size of the desulfurized gypsum after sieving is 20-50 μm.

[0035] Among them, tricalcium aluminate is prepared by grinding analytically pure calcium carbonate and aluminum oxide in a molar ratio of 3:1, mixing them evenly, and calcining them at high temperature.

[0036] Among them, tetracalcium aluminoferrite is industrial grade and has a particle size of 20 to 30 μm.

[0037] The fly ash is low-calcium fly ash, wherein the CaO content is ≤10wt%.

[0038] Wherein, the hydrotalcite is magnesium-aluminum hydrotalcite.

[0039] Among them, the rubber powder is industrial redispersible latex powder.

[0040] The retarder is industrial grade sodium alginate with a purity of ≥90wt%.

[0041] The preparation method of the low chloride ion leaching gypsum mortar is specifically implemented according to the following steps:

[0042] S1: Add rubber powder and retarder into water and stir evenly with a mixer to obtain an admixture solution;

[0043] S2: Evenly mix desulfurized gypsum, tricalcium aluminate, tetracalcium aluminate ferroferrate, fly ash and hydrotalcite powder to obtain a mixed powder;

[0044] S3: The admixture solution prepared in S1 and the mixed powder prepared in S2 are evenly mixed to obtain low chloride ion leaching gypsum mortar.

[0045] Wherein, in the preparation of low chloride ion leaching gypsum mortar, the amount of water added in S1 is 40% of the total mass of the powder in S2.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the components and reagents of the low chloride ion leaching gypsum mortar are the same but in different proportions. The low chloride ion leaching gypsum mortar of this embodiment includes the following components by weight:

[0048] 65 parts of desulfurized gypsum, 6 parts of tricalcium aluminate, 5 parts of tetracalcium aluminoferrate, 13.79 parts of fly ash, 10 parts of hydrotalcite, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0049] The preparation method is the same as Example 1.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that the components and reagents of the low chloride ion leaching gypsum mortar are the same but in different proportions. The low chloride ion leaching gypsum mortar of this embodiment includes the following components by weight:

[0052] 78.79 parts of desulfurized gypsum, 3 parts of tricalcium aluminate, 3 parts of tetracalcium aluminoferrate, 10 parts of fly ash, 5 parts of hydrotalcite, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0053] The preparation method is the same as Example 1.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that tricalcium aluminate and tetracalcium aluminoferrite are not used. This example is a low chloride ion leaching gypsum mortar, and the raw materials include the following components by weight:

[0056] 76 parts of desulfurized gypsum, 13.79 parts of fly ash, 10 parts of hydrotalcite, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0057] The preparation method is the same as Example 1.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 1 is that fly ash is not used. This example is a low chloride ion leaching gypsum mortar, and the raw materials include the following components by weight:

[0060] 83.79 parts of desulfurized gypsum, 3 parts of tricalcium aluminate, 3 parts of tetracalcium aluminoferrate, 10 parts of hydrotalcite, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0061] The preparation method is the same as Example 1.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that hydrotalcite is not used. This example is a low chloride ion leaching gypsum mortar, and the raw materials include the following components by weight:

[0064] 80 parts of desulfurized gypsum, 3 parts of tricalcium aluminate, 3 parts of tetracalcium aluminoferrate, 13.79 parts of fly ash, 0.2 parts of rubber powder and 0.01 parts of retarder.

[0065] The preparation method is the same as Example 1.

[0066] The chloride ion leaching rate is a direct indicator of the ion curing effect of desulfurized gypsum mortar. Therefore, in the experiment, the chloride ion content of the 28-day-cured desulfurized gypsum mortar after 3-day immersion was divided by the chloride ion content in the desulfurized gypsum as the chloride ion leaching rate. The results are shown in Table 1.

[0067] Table 1 Chloride ion leaching rate of desulfurized gypsum mortar prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0068] Magnesium phosphate cement test block Chloride ion leaching rate % Example 1 4.2 Example 2 2.3 Example 3 5.5 Comparative Example 1 12.5 Comparative Example 2 6.3 Comparative Example 3 10.2

[0069] Compared with Comparative Examples 1, 2 and 3, the chloride ion leaching rate of Example 1 is greatly reduced, indicating that the addition of tricalcium aluminate and tetracalcium aluminoferrate reduces the chloride ion leaching rate of desulfurized gypsum mortar; the addition of fly ash can reduce the transmission efficiency of chloride ions and thus reduce the chloride ion leaching rate; hydrotalcite can reduce the chloride ion leaching rate through its own physical adsorption.

[0070] Compared with Example 1, the contents of tricalcium aluminate and tetracalcium aluminoferrate in Example 2 are increased, indicating that the increase in the contents of tricalcium aluminate and tetracalcium aluminoferrate can improve the solidification effect of desulfurized gypsum on chloride ions.

[0071] Compared with Example 1, the hydrotalcite content in Example 3 is increased, indicating that the increase in the amount of hydrotalcite can improve the physical adsorption effect of chloride ions, thereby improving the solidification effect of desulfurized gypsum on chloride ions.

[0072] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, please refer to the relevant description of other embodiments. The numerical range described in the present invention includes all numerical values ​​within this range, and includes range values ​​composed of any two numerical values ​​within this range. Different numerical values ​​of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value. The technical features in the claims and / or the specification of the present invention can be combined, and the combination method is not limited to the combination obtained by reference relationship in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also the protection scope of the present invention.

[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A low chloride ion leaching gypsum mortar, characterized in that: The raw materials include the following components by weight: 65-80 parts of desulfurized gypsum, 3-6 parts of tricalcium aluminate, 3-5 parts of tetracalcium aluminoferrate, 10-15 parts of fly ash, 5-10 parts of hydrotalcite, 0.2-0.5 parts of rubber powder and 0.01-0.03 parts of retarder; The particle size of the tetracalcium aluminoferrite is 20 to 30 μm; The fly ash is low-calcium fly ash, wherein the CaO content is ≤10wt%; The retarder is sodium alginate, and the purity is ≥90wt%.

2. The low chloride ion leaching gypsum mortar according to claim 1, characterized in that: The desulfurized gypsum is a dry powder with a particle size of 20 to 50 μm.

3. The low chloride ion leaching gypsum mortar according to claim 1, characterized in that: The hydrotalcite is one or more of magnesium-aluminum hydrotalcite or hydrotalcite-like compounds.

4. The low chloride ion leaching gypsum mortar according to claim 1, characterized in that: The rubber powder is any one of industrial redispersible latex powder and building instant rubber powder.

5. The method for preparing low chloride ion leaching gypsum mortar according to any one of claims 1 to 4, characterized in that: The steps include: S1: Add rubber powder and retarder into water and stir evenly with a mixer to obtain an admixture solution; S2: Evenly mix desulfurized gypsum, tricalcium aluminate, tetracalcium aluminate ferroferrate, fly ash and hydrotalcite powder to obtain a mixed powder; S3: The admixture solution prepared in S1 and the mixed powder prepared in S2 are mixed evenly to prepare low chloride ion leaching gypsum mortar.

6. The method for preparing low chloride ion leaching gypsum mortar according to claim 5, characterized in that: In the preparation of the low chloride ion leaching gypsum mortar, the amount of water added in S1 is 30% to 45% of the total mass of the powder in S2.

Citation Information

Patent Citations

  • Functional admixture for treating desulfurized gypsum with high chloride ion content as well as preparation method and application of functional admixture

    CN113979665A